Volt-e a szocialista reformoknak eredménye? Osztálykülönbségek az iskolai végzettségben Magyarországon (Szociológiai Szemle, 2024)
Did socialist reforms have an impact on the Hungarian educational system? And if so, were the effects in the desired direction?The article answers the questions on the basis of a 24.829-strong empirical survey, restricted to respondents who were born between 1911 and 1960. According to the results of the cohort analysis the expansion of the mass education comenced before the transition to socialism, as well as the convergence between the levels of schooling of men and women. It follows that a more complex explanation, one which combines „socialist reform effects” with the thesis of industrialisation and social modernization arguments, might have to be invoked in order to explain the observed pattern of change.On the other hand the class based quotas of the first twenty years of socialism produced little in the way of results. Quotas were abandoned too soon to have a lasting influence on educational opportunities. The authors think that the quota system was also undermined while it was in place.